2010
DOI: 10.1107/s1600536810029417
|View full text |Cite
|
Sign up to set email alerts
|

(2-Methylphenyl)(phenyl)methanol

Abstract: In the title compound, C14H14O, the two benzene rings are almost orthogonal [dihedral angle = 87.78 (8) °]. The hy­droxy group lies approximately in the plane of its attached benzene ring [O—C—C—C torsion angle = −17.47 (17)°], and the hydroxyl and methyl groups lie to the same side of the mol­ecule and are gauche to each other. In the crystal, a hexa­meric aggregate mediated by a ring of six O—H⋯O hydrogen bonds occurs, generating an R 6 6(12) loop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Benzhydrols are widely used as intermediates for the synthesis of pharmaceuticals (Ohkuma et al, 2000). The crystal structures of 2-(5-bromo-2-methylphenyl)propan-2-ol (Zeng & Liu, 2010), 10,10-dimethylanthrone (Fun et al, 2010), (2-methylphenyl)(phenyl)methanol (Siddaraju et al, 2010), 9,9-dimethyl-9,10-dihydroanthracene (Siddaraju et al, 2011) and a N,N-dimethylamino-substituted analogue of the title compound (Gu et al, 2009) have been reported earlier. In view of the importance of the title compound, its crystal structure was determined.…”
Section: S1 Commentmentioning
confidence: 94%
See 1 more Smart Citation
“…Benzhydrols are widely used as intermediates for the synthesis of pharmaceuticals (Ohkuma et al, 2000). The crystal structures of 2-(5-bromo-2-methylphenyl)propan-2-ol (Zeng & Liu, 2010), 10,10-dimethylanthrone (Fun et al, 2010), (2-methylphenyl)(phenyl)methanol (Siddaraju et al, 2010), 9,9-dimethyl-9,10-dihydroanthracene (Siddaraju et al, 2011) and a N,N-dimethylamino-substituted analogue of the title compound (Gu et al, 2009) have been reported earlier. In view of the importance of the title compound, its crystal structure was determined.…”
Section: S1 Commentmentioning
confidence: 94%
“…For general background to the use of benzhydrols in pharmaceutical synthesis, see: Ohkuma et al (2000). For related structures, see: Ferguson et al (1995); Fun et al (2010); Siddaraju et al (2010Siddaraju et al ( , 2011; Zeng & Liu (2010); Gu et al (2009). For graph-set analysis of hydrogen bonds, see: Etter et al (1990); Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…For related literature on the background of this work, see: Ferguson et al (1995); Ohkuma et al (2000). For related structures, see: Narayanan et al (2011); Shah et al (2011); Siddaraju et al (2010); Zhang et al (2008); Zhang et al (2011). Data collection: SMART (Bruker, 2002); cell refinement: SAINT (Bruker, 2002); data reduction: SAINT; program(s) used to solve structure: SHELXTL (Sheldrick, 2008); program(s) used to refine structure: SHELXTL; molecular graphics: SHELXTL; software used to prepare material for publication: SHELXTL and local programs.…”
Section: Related Literaturementioning
confidence: 98%
“…For the use of the title compound in the perfume and pharmaceutical industries, see: Meguro et al (1985). For related diphenylmethanol structures, see: Betz et al (2011); Ferguson et al (1995); Siddaraju et al (2010). Table 1 Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%
“…Recently, the crystal structure of (2-methylphenyl) (phenyl)methanol (Siddaraju et al, 2010) and 2-(2-benzylphenyl)…”
Section: Sup-1mentioning
confidence: 99%